Horse monitoring project at ready steady Tokyo test event - Marlin, D. (2019)
Conditions during the Ready Steady Tokyo test event in August 2019 were thermally challenging,with Wet Bulb Globe Thermometer (WBGT)Index readings frequently in the region of 32-33°C. Despite this, horses coped extremely well with the conditions. The air-conditioned stables provided a temperature around 21-24°C without draughts through a fabric distribution ducting system. The high-roofedand naturally ventilated indoor training arena provided a thermal environment that was between the stable conditions and the outside conditions. The WBGT Index in the indoor arena never exceeded 29°C,even when exterior conditions reached ~35°C WBGT. All horses remained in good health for the duration of the event. On cross country day (13 August), the high WBGT Index, steep initial climb and sharp turns on the course produced a significant challenge for competing horses. Heart rates during cross country and blood lactate, heart rate and rectal temperature after crosscountry indicated that horses were working at close to maximal capacity. All possibilities must be explored to mitigate the effects of the likely climatic conditions, including reduction in distance appropriate for the conditions and bringing the cross country start time forward to avoid the highest WBGT conditions that would normally peak between late morning and mid-afternoon. As the WBGT Index readings recorded by the Tokyo Organising Committee of the Olympic and Paralympic Games (TOCOG) and the FEI showed some discrepancies due to differences of location and technology, consideration is required as to what WBGT measurements will be used forGames management decisions.Horses exercising at maximal intensity at WBGT Index values over ~30°C are at increased risk of early fatigue, errors, falls, injuries and heat-related illness. Historic record analysis and onsite data collectionshow that very high values of WBGT Index are frequently reached between 11:00 and 12:00 in Tokyo during the Games period. Competition and training schedules have been set to reflect this. However, the cross country at Sea Forest (SFC) is currently scheduled to end at approximately 12:00 and clearly it would be extremely advantageous for horse and athlete welfare if it could be completed by 11:00. Two innovative monitoring devices were tested during the event. The first of these was a new device from Polar which allows vets to obtain a horse`s heart rate rapidly and very accurately but also displaysthe ECG. This technology was found to be very easy to use, reliable and could be considered for use by teams during the Tokyo 2020 Olympic Games. The second technology that wasused was infrared thermal imaging (thermal cameras/thermography) as an aid to vetsand stewardsthroughmonitoringskin surface temperature. In thermally challenging conditions it can be easy for horses to become over-heated and a horse mayrapidlygo from being alright to at risk of heat exhaustion or heat stroke. Thermal imaging is a non-invasive, non-contact technology that allows the surface temperature of exercising horses to be measured at a distance of up to 15 metres. As aresult of making comparisons between surface temperatures of horses and their rectal temperature, we found that with the correct protocol,thermal cameras can be used to provide a rapid and accurate estimate of a horse`s rectal temperature. Consideration of how this technology may be deployed during Tokyo 2020 is currently underway.